Natural ventilation of residential building Atrium under fire scenario - Al-Waked, R. (Elsevier Ltd, 2021)
A residential block consists of two buildings connected via an Atrium is common nowadays because they could provide attractive, environment controlled and naturally lit spaces. The purpose of the current study is to undertake a performance based assessment of the proposed ventilation strategy and justify the performance through the use of computation fluid dynamics (CFD) approach. The three dimensional study utilized two available CFD packages: CFD ACE + for natural ventilation simulations and Fire Dynamic Simulator (FDS) for fire simulations. Four different louver opening areas were examined to see their effect on air speed and temperature of air within the Atrium. Another five scenarios were examined with the existence of fire within the Atrium. Results showed that the natural ventilation solution is dependent on ambient conditions outside the Atrium. Therefore, operable louvres are recommended to be fully closed under extreme weathers and to have it fully opened at an outdoor temperature of 19 °C-27 °C. In the case of a fire being ignited within the Atrium, it is found that the location of the fire has a significant impact on the air quality within the Atrium. It is found that when the fire is located in the open void area to the east of the Atrium, a simple ventilating strategy is capable of providing the required ventilating capacity to maintain the Atrium safe for evacuating the occupants. When the fire is located at the lifts and stairs area, however, the ventilation strategy requires a more sensitive approach. It is found that the natural ventilation approach failed in extracting the smoke out of the Atrium (Lifts lobby) unlike when the fire was located in the void area. However, the air temperature within the Atrium is found to meet the design requirements of lower than 60 °C. © 2021 The Author(s).